Improvisation in project management: A praxeology. Issue 2 (February 2015) - Klein, Louis; Biesenthal, Christopher; Dehlin, Erlend
Abstract Project management is complex and therefore a fruitful ground for creative, spontaneous and intuitive applications of particular theories to meet the stated objectives in a constantly changing environment. This form of work is defined as improvisation, which describes a pragmatic approach of applying existing theories in novel ways to deliver a successful project. The combination of a solid theoretical knowledge base and improvisational practices is our approach to conceptualise a praxeology of resilient project management. A praxeological mindset is well suited to improve our current understanding of project management towards a more resilient meta-theory of project management that is able to address complexity. This paper contributes to the current debates in project management, as it develops a foundation for bridging theory and practice. Providing sound, practice-related theories stimulates fruitful debate between the various professions of the project-management community, which will help the field to further mature and grow.